Reform report (2005)
A. Competition Format B. Referee Selection Procedure C. Public Relations D. Marketing (Both Taekwondo and WTF) E. Doping F. Development & Solidarity G. Membership (National Associations) H. WTF Organizational Structure I. HQs Administration J. Development of Ethics Guidelines K. Finance L. Competition Management M. International Relations N. IT and Internal Communications O. Reform Fund